STRATEGI POLA ASUH ORANG TUA MILENIAL UNTUK MENCEGAH PELECEHAN SEKSUAL DI DESA SETROHADI KECAMATAN DUDUK SAMPEYAN KABUPATEN GRESIK - Jauhari, Ahmad Zakki; Sholikhah, Khotimatus; Ayu, Intan (Fakultas Agama Islam, 2024)
Parenting strategies to prevent sexual harassment are important to implement in the current era of increasingly developing technology. Likewise, parents need to have parenting strategies to prevent sexual harassment from being applied to their children so as to create a generation of the nation's children with good morals and achievements. This research aims to determine parenting strategies for preventing sexual harassment in Setrohadi Village, Duduk Sampeyan District, Gresik Regency. This research method uses a qualitative descriptive approach, namely research that produces descriptive data in the form of other people's written or spoken words and observable behavior. The techniques used are data collection techniques, namely observation, interviews and documentation. The results of the research can be concluded as follows: 1) Parenting Strategy for Preventing Sexual Harassment in Setrohadi Village, Duduk Sampeyan District, Gresik Regency, namely; a) Provide an understanding of religion; b) Openness between parents and children; c) Supervision of technology access; d) Building trust with children; e) Tell children about the risks of sexual abuse. 2) Forms of Prevention Efforts Taken to Avoid Sexual Harassment in Setrohadi Village, Duduk Sampeyan District, Gresik Regency, namely; a) Deepen religious knowledge; b) Increase public awareness of sexual harassment; c) Get used to a healthy lifestyle.